Geração de biogás a partir de resíduos das agroindústrias de banana e palmito pupunha - Vidal, Thaís Cristina Morais (2014)
Concern about the depletion of traditional fossil fuels and the resulting greenhouse effect caused by the use of these have become increasingly larger, which makes it necessary to search for alternative sources of clean energy generation. This study aims to determine the production of biogas by mixing waste agribusiness banana and palm pupunha, besides the analysis of effluents and subsequent verification of the reduction of the organic load of the raw materials used. Were used in batch digesters, made with PVC and fed different levels of mixtures of biomass, enabling the qualitative and quantitative verification of biogas obtained. Average yields significant biogas, up to 39,29 and 29,60 L and loads that reached up to 73,96 % reduction was found.